Nitrogen metabolism in the phototrophic bacteria Rhodocyclus purpureus and Rhodospirillum tenue. - Masters, R A (1983)
Studies of the nitrogen nutrition and pathways of ammonia assimilation in Rhodocyclus purpureus and Rhodospirillum tenue have shown that these two seemingly related bacteria differ considerably in aspects of their nitrogen metabolism. When grown photoheterotrophically with malate as carbon source, R. purpureus utilized only NH4+ or glutamine as sole nitrogen sources and was unable to fix N2. By contrast, R. tenue was found to utilize a variety of amino acids as nitrogen sources and was a good N2 fixer. No nitrogenase activity was detected in cells of R. purpureus grown on limiting ammonia, whereas cells of R. tenue grown under identical conditions reduced acetylene to ethylene at high rates. Regardless of the nitrogen source supporting growth, extracts of cells of R. purpureus contained high levels of glutamate dehydrogenase, whereas R. tenue contained only trace levels of this enzyme. Alanine dehydrogenase activity was absent from both species. We conclude that R. purpureus is incapable of fixing molecular nitrogen and employs the glutamate dehydrogenase pathway as the primary means of assimilating NH4+ under all growth conditions. R. tenue, on the other hand, employs the glutamine synthetase/glutamate synthase pathway for the incorporation of NH4+ supplied exogenously or as the product of N2 fixation.